PENGARUH KANDUNGAN INFORMASI ARUS KAS, LABA KOTOR DAN SIZE PERUSAHAAN TERHADAP EXPECTED RETURN SAHAM PADA EMITEN LQ 45 - - Mafudi (JAFFA, 2014)
The aims of this paper is to analyze the effects of  cash flow (including operating, inveting, and financing), gross profit, and firm size to the stock expected return.  The population of this study is emiten LQ 45 for period 2008-2012.  Implementing linier regression analysis, the result showes that all independent variables affect significantly to te stock expected return..  Elasticity test proofs that the fim size has the most dominat effect to the stock expected return.